â- structure properties ofZn-Phthalocyanine organic semi-conductor (Baghdad Science Journal, 2025)
The x-ray fluorescence (XRF) of Znpc molecule with (flow of Ar) and Znpc molecule with (grow in N2) showed two peaks at (8.5and 9.5 Kv) referring to orbital transition ) K?-shell & K?-shell) respectively. The study of x-ray diffraction (XRD) where it was observed good growth of the crystal structure as a needle by the sublimation technique with a ?-phase of (monoclinic structure ) . Using Bragg equation the value of the interdistance of the crystalline plane (d-value) were calculated. We noticed good similarity with like once in the American Standards for Testing Material (ASTM) .Powder Diffraction File (PDF) Program was used to ensure the information obtained from (ASTM) . The output of (PDF) was compared with celn program, where the value of angle(2?( , crystal axis (a,b,c) and axial angles (?,?,?) were calculated.The partical grain size of H2PC was between (27-35)nm, while for ZnPC was between (17-50)nm by applying of Schreer equation. The results are in a good agreement with c-size program.The morphology was distinguished by optical microscope of (200X) magnification for a tini-fiber like a (whisker needle type) with blue color, porous nature and short term structure. The diameter of the fiber H2PC and ZnPC were (20 and 16?m) respectively.